Carryover effects of environmental stressors influence the life performance of brown trout - Louhi, Pauliina; Pettinau, Luca; Härkönen, Laura S.; Anttila, Katja; Huusko, Ari (Ecological Society of America, 2023)
Carryover effects of environmental stressors occur when experiences of the environment in earlier life stages or seasons influence the performance of individuals later in life. These can be especially critical for species that have diverse developmental transition periods in their life cycle, such as salmonid fish. Sublethal changes in metabolism, size, or growth experienced in early life stages may have a long-lasting effect on the subsequent life performance of these species, but very few studies have formally tested these changes in relation to environmental stressors. Here, we investigated whether different types of fine sediment result in carryover effects that change the life performance of migratory brown trout. First, we manipulated the early habitat conditions of brown trout through the life stages from egg to fry by incubating them in varying substrate treatments (i.e., gravel without added sediment, gravel with added fine sand, and gravel with added organic matter). Exposure to fine sediment during early development had serious effects on the metabolism, size, escape responses, timing of emergence, and potential survival of early life stages. These carryover effects were persistent and remained present over the critical life shift from relying on parentally provided resources as immobile eggs to independent exogenous feeding as parr. Second, fish were relocated as parr to either their original or different treatment environments and their metabolism, size, and growth were reanalyzed. The effects of environmental stress were observed later in their life cycle when fry from the gravel treatment were relocated to sand or organic-rich treatments. These were found to be significantly smaller in size and had a higher metabolic rate than fry maintained in their original treatment environment. Together, our study experimentally demonstrated that the carryover effects of environmental stressors experienced in early stages may influence the fitness outcomes of migratory fish later in life. We suggest that sublethal environmental stressors should be better considered in restoration schemes and management strategies to reverse the current trend of declining salmonid populations.
Keywords: brown trout; carryover effects; environmental stressors; escape responses; fine sediment; metabolism